A reactive continuous chromatographic process for protein PEGylation. Issue 2 (4th January 2016) - Ingold, Oliver; Pfister, David; Morbidelli, Massimo
Abstract : A multicolumn process in the form of a twin-column MCSGP unit is fitted with an additional column to perform a on-column protein PEGylation reaction. Thanks to this rMCSGP process, the conjugation reaction is obtained simultaneously with the purification of the products at high yield and high conversion of the protein. Abstract : In a previous work, a batch on-column PEGylation process was developed and thoroughly investigated (Pfister et al., Reaction Chemistry & Engineering, 2016). A mathematical model was derived and its predictions compared with experimental data were obtained under various conditions. As an alternative, a multicolumn counter-current chromatographic setup is considered to turn the batch on-column PEGylation process into a continuous one. Using the parameters previously estimated, the continuous chromatographic process in the form of a reactive multicolumn counter-current solvent gradient purification (rMCSGP) process was simulated and the performance of the process was assessed. Batch experiments were performed to show the feasibility of the method and to determine the parameters specific to the design of multicolumn processes. It is shown that the rMCSGP process can improve the throughput, purity and yield for the production of mono-PEGylated protein.